Greater Financial Disclosures in Singapore: Boon or Curse? - Choo, Teck Min (Institutional Knowledge at Singapore Management University, 1997)
The paper presents arguments for and against greater financial disclosure in Singapore. The arguments for greater financial disclosure center around meeting the diverse needs of an increasingly sophisticated pool of investors. Another argument for voluntarily increasing financial disclosure is the potential threat of government intervention in the setting of financial disclosure requirements that may even be more stringent. These arguments have to be balanced against the counter-arguments that first, people can only process limited amounts of information. Second, do the benefits to users outweigh the costs of collection, collating, and disseminating the additional information? Third, there is the confidentiality issue of greater disclosure. Recent empirical data on the status of voluntary disclosure in Singapore and reporting on social responsibility are also discussed.